Measuring the efficacy of HVAC particle filtration over a range of ventilation rates in an office building. (15th October 2018) - Ben-David, Tom; Wang, Sheng; Rackes, Adams; Waring, Michael S.
Abstract: Ventilation rates (VR) higher than minimum standards can have positive impacts on occupant productivity and wellbeing. However, higher VRs amplify concentrations of indoor particles of outdoor origin, and thus also exposure outcomes. This study explored the efficacy of using high versus low efficiency filtration (i.e., MERV 14 or 15 versus MERV 8 filters) to control indoor particles over a range of ventilation air exchange rates (1.0, 2.4, and 5.4 h −1 ) in the third floor of an office building, served by its own air handling unit. During each of 66 test days, a single combination of filter and VR were used, and time-resolved fine particulate matter (PM2.5 ) and ozone concentrations and airflow rates were measured in the supply, return, and outdoor airstream. The return air was taken as a surrogate for the average state of indoor air in the office's third floor. While higher VRs increased PM2.5 indoor/outdoor (I/O) concentration ratios, filtration was more impactful on I/O ratios than the VR, as most cases with MERV 14 or 15 filters and highest VR resulted in lower PM2.5 I/O ratios than cases with a MERV 8 filter and lowest VR. Concentration and flow data were used to compute real-time in-situ removal efficiencies of each filter, and MERV 8, 14, and 15 filters had mean (standard deviation) PM2.5 removal efficiencies of 0.16 (0.12), 0.73 (0.091), and 0.72 (0.10) at 100% outdoor air, as well as ozone removal efficiencies of 0.16 (0.10), which were unaffected by filter type but varied somewhat with ventilation rate. Highlights: Effect of filtration at range of ventilation rates on PM2.5 and ozone was tested. Combinations of filters and ventilation rates were used in a 66-day experiment. PM2.5 and ozone I/ratios and in-situ removal efficiencies were calculated. Median PM2.5 filter efficiencies were 0.21 (MERV 8); 0.70 (MERV 14); 0.64 (MERV 15). Ozone removal was independent of filter type, with mean efficiency = 0.16